2022
DOI: 10.1590/0034-7167-2022-0049
|View full text |Cite
|
Sign up to set email alerts
|

Intravenous therapy device labeling in Intensive Care Units: an integrative review

Abstract: Objectives: to synthesize the evidence on intravenous device labeling used to identify medications administered to patients in Intensive Care Units, with a view to preventing medication errors. Methods: an integrative review, in the LILACS, IBECS, Embase, MEDLINE, Scopus, Web of Science and CINAHL databases, from November to December 2021, using descriptors and selection criteria. Data were collected in 11 articles and subsequently classified, summarized and aggregated. Results: pre-designed labels, with pre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0
17

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(20 citation statements)
references
References 21 publications
0
3
0
17
Order By: Relevance
“…Erros durante a administração de anestesia podem ter consequências sérias, ressaltando a necessidade crucial de manter elevados padrões de segurança para preservar a integridade e bem-estar do paciente 1,8 .…”
Section: Resultsunclassified
See 1 more Smart Citation
“…Erros durante a administração de anestesia podem ter consequências sérias, ressaltando a necessidade crucial de manter elevados padrões de segurança para preservar a integridade e bem-estar do paciente 1,8 .…”
Section: Resultsunclassified
“…A obstrução das vias aéreas é uma preocupação significativa, podendo ocorrer devido a múltiplos fatores, como relaxamento da musculatura da garganta, queda da língua para trás ou edema das vias aéreas. Isso pode levar à hipoxemia e, em casos graves, à parada cardíaca se não for prontamente tratada 2,8 .…”
Section: Complicações Respiratórias Gravesunclassified
“…However, a previous study conducted by the authors showed that there are currently gaps in the recommendations for labelling standards of devices used in care scenarios that assist critically ill patients. 10 In addition, the existing standard for label standardization-International Organization for Standardization (ISO) number 26825/2021-is limited to single-dose drugs used in anaesthesia and with syringe-type devices. 19 Therefore, it is necessary to summarize the relevant literature on IV drug delivery device labelling in order to identify and summarize standards that can guide the development of device labels and their…”
Section: Introductionmentioning
confidence: 99%
“…Labelling standards for syringes, bags, and IV lines are strategies that strengthen the safety of institutional medication systems, that is, technologies that prevent the misidentification of IV drugs administered to critically ill patients. However, a previous study conducted by the authors showed that there are currently gaps in the recommendations for labelling standards of devices used in care scenarios that assist critically ill patients 10 . In addition, the existing standard for label standardization‐International Organization for Standardization (ISO) number 26825/2021—is limited to single‐dose drugs used in anaesthesia and with syringe‐type devices 19…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation